Development, standardization and methods of judicial audit in the Republic of Kazakhstan - Аkаn А.; Yerzhanov, M.S.; Yerzhanov А.М.; Syzdykova, E.Zh. (BUKETOV BUSINESS REVIEW, 2023)
Object: To investigate conceptual foundations of judicial audit and determine its place in the system of audit and consulting services. Methods: General methods of scientific cognition were used while working on this paper: empirical research (observation, comparison, analysis, synthesis (generalization); theoretical research (ascending from abstract to concrete, from general to specific, and from phenomenon to essence, dedication of selected parts of the object, identification of cause-and-effect relationships); rules of formal logic; and a systematic approach. Findings: In the face of the growing number and scale of fraud and other economic offenses, judicial audit services are becoming especially relevant. This paper discusses regulation of judicial audit. Elements of the national standard of judicial audit proposed by the authors are described. Main stages of organization and methods of judicial audit are disclosed. Conclusions: A forensic audit requires knowledge of accounting and general audit procedures, and expert knowledge of the legal basis for such an audit. The judicial auditor must be specially trained in audit procedures. A forensic audit entails additional procedures that must be performed in addition to the standard audit procedures. That said, a forensic audit is a detailed task that requires competence both in accounting and in audit methods and procedures, as well as a professional legal understanding. A forensic auditor must be aware of numerous types of fraud, as well as evidence collection procedures.